2017
DOI: 10.26420/austinjorthopaderheumatol.2017.1047
|View full text |Cite
|
Sign up to set email alerts
|

Primary Malignant Melanoma of the Lumbar Spine

Abstract: Low Back Pain (LBP) or Lumbago is a leading cause of disability in the United States. There are several etiologies including but not limited to muscle strains, discherniation, vertebral instability and fractures. Most serious however are metastatic neoplastic processes, which invade the spine, spinal cord, and nerve roots potentially causing significant neurologic and functional compromise. Primary tumors of the spine are extremely rare, even rarer are primary melanomas of the spine [1]. We present a rare case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The final possibility considered was that the vertebral melanoma in our patient could have been a primary neoplasm. In humans, primary vertebral melanoma is incredibly rare, and the authors identified only two case reports in the literature that documented one cervical 34 and one lumbar 35 primary neoplasm. Giuliano et al 36 reported that the primary neoplasm could not be detected in 5.6% of 980 patients with malignant melanoma, and there are a small number of reports of vertebral melanomas suspected to be secondary to an unknown primary neoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final possibility considered was that the vertebral melanoma in our patient could have been a primary neoplasm. In humans, primary vertebral melanoma is incredibly rare, and the authors identified only two case reports in the literature that documented one cervical 34 and one lumbar 35 primary neoplasm. Giuliano et al 36 reported that the primary neoplasm could not be detected in 5.6% of 980 patients with malignant melanoma, and there are a small number of reports of vertebral melanomas suspected to be secondary to an unknown primary neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The final possibility considered was that the vertebral melanoma in our patient could have been a primary neoplasm. In humans, primary vertebral melanoma is incredibly rare, and the authors identified only two case reports in the literature that documented one cervical 34 and one lumbar 35 primary neoplasm. Giuliano et al 36 .…”
Section: Discussionmentioning
confidence: 99%